2015
DOI: 10.5539/mas.v9n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Situation Control of Unmanned Aerial Vehicles for Road Traffic Monitoring

Abstract: This paper aims to introduce an approach to the organization of road traffic monitoring by the means of unmanned aerial vehicles (UAVs), which is based on the automatic situation control of UAVs. The research includes analysis of existing methods of on-board automatic detection of emergency and abnormal traffic situations with UAV artificial vision systems (AVS), preliminary classification of these situations including the allocation of emergencies and disastrous situations. The paper presents the choice of UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Deep learning methods applied on images captured from UAVs have an actual significance in CPSs. For instance, previous studies proposed the deep learning approach for detecting and counting cars for images captured from UAVs [161], road traffic monitoring from UAVs [162], and inspecting civil infrastructure systems [28,163].…”
Section: ) Effective Visual Data Analysis Algorithmsmentioning
confidence: 99%
“…Deep learning methods applied on images captured from UAVs have an actual significance in CPSs. For instance, previous studies proposed the deep learning approach for detecting and counting cars for images captured from UAVs [161], road traffic monitoring from UAVs [162], and inspecting civil infrastructure systems [28,163].…”
Section: ) Effective Visual Data Analysis Algorithmsmentioning
confidence: 99%
“…Deep learning techniques applied on images taken from UAVs have also gained a lot of importance in monitoring and search and rescue applications, such as jellyfish monitoring [70], road traffic monitoring from UAVs [71], assisting avalanche search and rescue operations with UAV imagery [72], and terrorist identification [73]. In [72,73], the use of pretrained CNN models for feature extraction is worth noting again.…”
Section: With Image Sensorsmentioning
confidence: 99%
“…In this study a cascading approach to the vehicle recognition has been defined. The works (Kim and Chervonenkis, 2015;Abramov et al, 2015) have suggested using the image segmentation into superpixels followed by their association in regions, this approach is also used in proposed algorithm herein. These works were inspired by (Choi and Yang, 2009) paper which applies mean shift segmentation in the Luv color space in order to extract blobs (superpixels) of the image.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned work by (Kim and Chervonenkis, 2015) describes in detail the methodology of the use of UAV for road traffic monitoring and proposes an approach based on the recognition and classification of severity traffic situation. In this study we described the UAV automatic control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation